Comparing the Times Between Successive Failures by Using the Weibull Distribution with Time-Varying Scale Parameter - Celik, Nuri; Konyalioglu, Aziz Kemal (Springer-Verlag Singapore Pte Ltd, 2022)
In this study, we propose a method for comparing three or more means of time between two failures (TBF) for different systems or processes. Traditionally, one-way ANOVA is used to compare the means of three or more group, however, this method is based on the normal distribution assumption. For this reason, we propose one-way ANOVA model whose error distribution is the Weibull distribution with time-varying scale parameter. Since, in reliability analysis, the TBFs are generally not identically and independently distributed and the Weibull distribution with time-varying scale parameter has been proposed to analyse the TBFs. We obtain the estimations of the unknown parameters with the maximum likelihood methodology. We also propose a new test statistic for testing the difference mean time failures. A Monte Carlo simulation study is performed for comparing the power of this proposed test statistics with the traditional ones. Simulation results show that the proposed methodologies are more preferable.
21st International Symposium on Production Research (ISPR) - Digitizing Production System -- OCT 07-09, 2021 -- ELECTR NETWORK
Keywords: Failure process; Weibull distribution; Time-varying parameter; One-way ANOVA